2015 Russell Ross Memorial Lecture in Vascular Biology: Protective Autoimmunity in Atherosclerosis. Issue 3 (March 2016) - Ley, Klaus
Abstract : Atherosclerosis is an inflammatory disease of the arterial wall. It is accompanied by an autoimmune response against apolipoprotein B-100, the core protein of low-density lipoprotein, which manifests as CD4 T cell and antibody responses. To assess the role of the autoimmune response in atherosclerosis, the nature of the CD4 T cell response against apolipoprotein B-100 was studied with and without vaccination with major histocompatibility complex-II–restricted apolipoprotein B-100 peptides. The immunologic basis of autoimmunity in atherosclerosis is discussed in the framework of theories of adaptive immunity. Older vaccination approaches are also discussed. Vaccinating Apoe −/− mice with major histocompatibility complex-II–restricted apolipoprotein B-100 peptides reduces atheroma burden in the aorta by ≈40%. The protective mechanism likely includes secretion of interleukin-10. Protective autoimmunity limits atherosclerosis in mice and suggests potential for developing preventative and therapeutic vaccines for humans.